Does Banking Union Worsen the EU's Democratic Deficit? The Need for Greater Supervisory Data Transparency1. (8th December 2014) - Gandrud, Christopher; Hallerberg, Mark
Abstract Does banking union exacerbate the European Union's democratic deficit? Using Scharpf's 'input' and 'output' legitimacy concepts, it is argued in this article that its design does worsen the democratic deficit. There are good reasons to limit 'input legitimacy' for politically independent institutions. 'Output legitimacy' is then even more relevant. Transparency is a key part of 'output legitimacy'. It enables actors to judge whether the regulator is acting in the public's interest and can improve their outputs. This article focuses on the banking data that the supervisors collect. Data available to the European public is evaluated and compared to America's banking union. European practices are not comparable in terms of availability or detail. An original survey of relevant officials is conducted, which results in the finding that only 11 of 28 Member States release any information on the banks they supervise. Both EU and national supervisors should provide publicly available, timely and consistent individual bank data.